Influence of sintering temperature on mechanical and tribological characteristics of copper based composite reinforced by 2D hybrid material - Nautiyal H.; Gautam R.K.S.; Singh S.; Goswami R.; Gautam G.; Raturi A.; Khatri O.P.; Tyagi R. (My University, 2025)
The effect of sintering temperature on the mechanical and tribological characteristics of 2D phase reinforced copper-based composite has been investigated in the present study. The Cu-based composites containing 2 wt. % of(GO + MoS2)NP were sintered at different temperatures (1023, 1073, 1123, and 1173 K) by microwave sintering process. The microstructural features observed by SEM and HRTEM of composites suggest that as the sintering temperature increases (GO + MoS2)NP pocket formation tendency also increases, which also governs the mechanical and tribological characteristics of composites. As the sintering temperature elevated, the ultimate tensile strength of the composite decreases, whereas friction and wear rate decrease with increase in temperature up to 1123 and beyond 1123 increase in friction and wear has been observed. The decrease in strength with increasing sintering temperature has been attributed to the grain size increment and increase in (GO + MoS2)NP pocket size at the grain boundaries. However, the decrease in friction and wear rate has been ascribed to the ease of extrusion of (GO + MoS2)NP from the pockets for the composites sintered at high temperature, rather than extrusion of (GO + MoS2)NP of fillers from the intra-grainular sites, i.e., for the composites sintered at lower temperature. © IMechE 2023.